The effect of lateral thinking strategy with virtual reality glasses on visual perception and some complex football skills at the Al-Diwaniyah Talent Center - Jabr, Prof. Dr. Habib Shaker; Hassan, Prof. Dr. Auras Naama; Kahat, Prof. Dr. Thamer Hussein; Ahmed, Prof. Dr. Ali Mohammed Jawad (Sulaimani Journal for Humanities, 2026)
This research aims to identify the differences between the pre-test and post-test in learning some complex football skills at the Talent Center. The field research procedures involved the researchers using an experimental design with equivalent groups. The current research population consisted of (30) players from the Talent Center in Al-Diwaniyah Governorate for the 2023-2024 training season. All players were under 17 years old. (2) goalkeepers and (8) outfield players were excluded in the pilot study, leaving (20) players. The sample was randomly divided into two groups (experimental and control), each containing (10) players. The researchers then implemented the lateral thinking strategy with virtual reality headsets for two months, at a rate of three educational units per week (24 units total), with the experimental group. The control group followed the coach's curriculum. Based on the post-tests and the research results, the researchers concluded that the lateral thinking strategy with virtual reality headsets had a positive and effective impact on improving complex skills compared to the control group. Control group
Keywords: Lateral thinking strategy; virtual reality headset; complex skills; football talent center players